A case of hemolytic-uremic syndrome that developed in a 5-year-old child due to acute intestinal infection with hemocolitis - O. V. Molochkova; S. B. Orekhova; R. V. Ovechkin; V. S. Vyshlova; V. V. Glukhova; O. B. Kovalev; N. Yu. Egorova; A. B. Chashchukhina; V. A. Masyakin; E. P. Egorova; A. A. Sakharova; A. G. Okhtyarkina (LLC "Diagnostics and Vaccines", 2024)
Purpose: to demonstrate a case of hemolytic-uremic syndrome (HUS) in a 5-year-old child associated with an acute intestinal infection of unknown etiology, occurring with hemocolitis. Results. During clinical and laboratory observation, edematous syndrome, oligoanuria, severe microangiopathic hemolytic anemia (decrease in hemoglobin, haptoglobin, increase in Lactate dehydrogenase), thrombocytopenia, consumption coagulopathy, hyperazotemia, acute kidney injury (AKI) according to KDIGO grade 2 (increase in serum creatinine more than 2 times) developed. As part of complex therapy with balanced crystalloid solutions with stimulation of diuresis, it was possible to achieve rapid restoration of diuresis on the 2nd day of hospital stay without the use of renal replacement therapy; he also received antibiotics, anticoagulants, transfusion of fresh frozen plasma and red blood cell suspension. Hyperazotemia was relieved within 5 days, as was thrombocytopenia. The follow-up recovery of renal function showed.